Interleukin-1 receptor associated kinase (IRAK)-M -mediated type 2 microglia polarization ameliorates the severity of experimental autoimmune encephalomyelitis (EAE). (August 2019) - Liu, Baozhu; Gu, Yong; Pei, Shanshan; Peng, Yu; Chen, Jinyu; Pham, Lan V.; Shen, Hai-Ying; Zhang, Jun; Wang, Honghao
Abstract: Toll-like receptor 4 (TLR4) play a key role in activating the innate immune system during pathogen recognition. In the pathogenesis of multiple sclerosis (MS), activated TLR4 together with myeloid differentiation primary response gene 88 (MyD88) produce an inflammatory microenvironment that promotes the differentiation of microglia into the M1 phenotype, who plays a key role in the pathogenesis of MS. Interleukin-1 receptor-associated kinase (IRAK)-M is specifically expressed in microglia in central nervous system (CNS) and act as a negative regulator of TLR4-MyD88 signaling pathway. Moreover, previous studies have shown that IRAK-M promotes the differentiation of type 2 microglia; however, its role in MS has not been explored. In the present study, we demonstrated that IRAK-M expression is elevated during EAE, and IRAK-M −/− mice significantly accelerated course and increased severity of disease, accompanied by a visible increase of the M1 microglia infiltrated. In conclusion, these data indicates that IRAK-M significantly improves EAE onset through down-regulation of the TLR4-MyD88 signaling pathway, which finally leads to differentiation of M2 phenotype in the microglia. Our study suggests that IRAK-M may be a potential therapeutic target for the treatment of MS. Highlights: The expression of IRAK-M is significantly increased during EAE. IRAK-M improves the clinical symptoms and pathological manifestations of EAE. IRAK-M inhibits NF-κB signaling and activation of STAT1. IRAK-M promotes M2 polarization of microglia and inhibits M1 polarization during EAE both in vivo and vitro.